On recognition of simple group L2(r) by the number of Sylow subgroups - Khalili Asboei, Alireza; Mohammadyari, Reza (Acta Scientiarum. Technology, 2014)
Let G be a finite group and n_{p}(G) be the number of Sylow p- subgroup of G. In this work it is proved if G is a centerless group and n_{p}(G)=n_{p}(L_{2}(r)), for every prime p in pi (G), where r is prime number, r^2 does not divide |G| and r is not Mersenne prime, then L_{2}(r)<=G<=Aut(L_{2}(r).